Immunization Clinic Management Model in the Situation of Coronavirus Disease 2019, Phiman Subdistrict, Mueang District, Satun Province - หิมมา อภิชญา (Journal of Health Science of Thailand, 2023)
This action research aimed to develop an immunization clinic operation model to suit the situation of the outbreak of COVID-19 and to compare the performance of the immunization clinics before and after the use of the developed model, as well as to assess the satisfaction of parents after the service model adjustment in the immunization clinics. The samples were 40 parents of children in immunization clinics by purposive sampling to collect data (between January 2022 - April 2022). Data were collected form the samples before and after receiving services in the immunization clinic; and interviews were conductedwith parents of children from birth to 5 years old in Phiman Community Health Center. The results showed that the new format took less than 90 minutes for the overall services provision which reduced congestion in the situation of the COVID-19 epidemic. The level of satisfaction on the vaccination service in newborns - 5 years of age was at a very satisfactory level.